Sustainable electrochemical devices based on earth-abundant materials for solar energy harvesting and storage - Said, Menna Tullah Samir (AUC Knowledge Fountain, 2019)
Over the past two decades, earth has witnessed a seminal growth in the global energy consumption rates accompanied by drastic Carbon dioxide emissions in the atmosphere. Recent callings for sustainable energy systems that can offset the carbon footprint made it inevitable to develop technologies that provide clean fuel alternatives to fossil fuels. Hydrogen can be that alternative as it is an it only produces water as a byproduct during combustion. However current commercial hydrogen production practices are energy consuming, and get their energy from fossil fuels. Solar energy, can be harvested with semiconducting materials. Consequently, it became of great necessity to develop semiconducting electrodes that can efficiently convert solar energy to electrical energy used in the splitting of water for the production of hydrogen. In the first part of this thesis, earth abundant metal, Titanium (Ti), was used to design electrodes that provide the reaction surface upon which water is split into Hydrogen. On a different note, the current commercial energy storage devices still face performance limitations, have high maintenance cost, and are not eco-friendly. Electrochemical supercapacitors hold the potential of being the next generation of efficient and clean energy storing devices. Their fast charge/discharge rates make them the perfect storing devices for peak power delivery applications contrary to batteries. However, supercapacitors are still underdevelopment and face major challenges such as relatively low energy density, performance degradation, and high cost. In order to overcome these limitations a lot of research is carried on the design of efficient, cheap, and stable electrode materials. The emergence of transition metal oxides as an active material for solar cells have encouraged the research of using them as electrode materials for supercapacitors. New strategies are developed for the fabrication of nanostructured mixed oxides fibers, incorporated with carbon based materials. These methods are expected to improve the capacitive performance and cyclic stability of the metal oxides electrodes. In the second part of the thesis, we propose a synthesis route for the fabrication of binder-free Manganese and Vanadium mixed oxides nanofibers electrodes for supercapacitors.